A gente precisa ter tempo pra gente: as narrativas dos(as) jovens do Poço da Draga sobre o aprender a ser e o aprender a viver juntos no tempo-espaço do lazer - Tereza Nair de Paula Pachêco (2017)
This study aims to establish possible relationships (approximations or distances) between the leisure enjoyment of the Poço da Draga youth community with the pillars of education / knowledge, specifically learning to be and learning to live together. The youth segment presents an intersection with the composers of social reality, situating itself in the historical, social, cultural and political terrain of the Brazilian scenario. In this context, the characteristics of the young people of Poço da Draga are pointed out. About the methodology, a qualitative, bibliographical and field research was carried out. Semi-structured interviews were conducted with ten young people (five girls and five boys) and two residents of Poço da Draga. The analysis / interpretation of the data was guided by the Marxist dialectic. According to the two residents, the community resists the imperatives of the capital and the dictates of the tourism industry, being surrounded by problems that mark the Poço da Draga youth (drugs, homicides, violence, pregnancy, difficult insertion in the Labor market and education etc).) According to the research, amidst a set of rights violations and the "forgetting" of the public power with that place, Poço da Draga (about) lives, protagonizes its history; Is not a passive "hostage" and "subject" in the face of the problems that surround him, facing them every day.The young people present contact with the sport in terms of leisure practice and are distanced from domestic and family obligations in the description of their routines. The young people present as leisure practices: watching movies, series, shows and shows; reading; Tours; swim on the beach; Watch the sunset etc. In their routines, they report on the domestic and family obligations that impact on the leisure experience. For young people, learning to be in the time-space of leisure materializes in personal achievements; In self-confidence and in the expansion of self-esteem, distancing oneself from it when there are no similar experiences. Some of the interviewees pointed out that it is easy to be as they are because they believe in themselves; Others said that it is difficult, due to the current situation. For them, leisure is conducive to the knowledge of the body, the mind, the way they are; Reflection on life; the Liberty; To contact with nature. For the young, learning to be is a moment of introspection; Of reflection; Of new knowledge; Of pondering about attitudes and how to deal with information; To recognize the other and social reality; Of problematizing the world; Of contact with other cultures; Confidence in you and your potential, etc. Some young people report being easy to be who they are as a result of their personal fulfillment. The difficulties lie in the incompatibility of personal values (understanding, tolerance) and those of the world (immediacy) and the fact that they are women, by the balance of tasks of home / child / study / work / family. For young people, learning to live together (fruit of leisure) is born in the collective coexistence; In the encounter and in the recognition of the other; In the centrality of social groups, friends and family. Thus, learning to be and to live together are conducive to the leisure of Poço da Draga's youth.